Consumer Satisfaction Using Airlines in Indonesia is Influenced by Several Factors - Fakhrudin, Arif; Kifni Yudianto; Djaelani Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of service quality through (tangible, reliability, responsiveness, assurance, and empathy) to customer satisfaction. This study uses independent variables, namely tangible, reliability, responsiveness, assurance, and empathy with dependent variable, customer satisfaction. After literature and field reviews and hypothesis formulation, the data in this study were collected through distributing questionnaires to 100 people using the Lion Air airline as a research sample. The sampling technique used was purposive sampling. The data analysis method used is a quantitative analysis of the validity and reliability test, multiple regression analysis, t test and f test and the determinant coefficient. The results of this study indicate that the indicators in this study are valid and reliable. In the tangible hypothesis test, reliability, responsiveness, assurance and empathy have a significant effect on consumer satisfaction partially and simultaneously. The determinant coefficient test results in this study obtained a determinant value of 0.326 which means that the magnitude of the influence of tangible variables (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) on customer satisfaction variables (Y) are by 32,6%.